2006
DOI: 10.1093/treephys/26.7.865
|View full text |Cite
|
Sign up to set email alerts
|

Changes in photosynthesis and leaf characteristics with tree height in five dipterocarp species in a tropical rain forest

Abstract: Variations in leaf photosynthetic, morphological and biochemical properties with increasing plant height from seedlings to emergent trees were investigated in five dipterocarp species in a Malaysian tropical rain forest. Canopy openness increased significantly with tree height. Photosynthetic properties, such as photosynthetic capacity at light saturation, light compensation point, maximum rate of carboxylation and maximum rate of photosynthetic electron transport, all increased significantly with tree height.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
111
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(135 citation statements)
references
References 48 publications
15
111
1
1
Order By: Relevance
“…8). This has been reported before for [N] A and M A in dipterocarp forests in Malaysia (Thomas and Bazzaz, 1999;Kenzo et al, 2006) with a tendency for taller trees to have a greater M A being an apparently general phenomenon (Poorter et al, 2009). This phenomenon will be dealt with in more detail in an accompanying paper utilising a much larger additional data set of individual trees for which only upper-canopy leaves had been sampled.…”
Section: Gradients In Nitrogen Phosphorus and Photosynthetic Capacitysupporting
confidence: 53%
See 2 more Smart Citations
“…8). This has been reported before for [N] A and M A in dipterocarp forests in Malaysia (Thomas and Bazzaz, 1999;Kenzo et al, 2006) with a tendency for taller trees to have a greater M A being an apparently general phenomenon (Poorter et al, 2009). This phenomenon will be dealt with in more detail in an accompanying paper utilising a much larger additional data set of individual trees for which only upper-canopy leaves had been sampled.…”
Section: Gradients In Nitrogen Phosphorus and Photosynthetic Capacitysupporting
confidence: 53%
“…5) is a consequence of species-to-species variations, this being closely linked to other aspects of their physiological strategy including leaf lifespans (Wright et al, 2004) and hydraulic characteristics (Santiago et al, 2004;Meinzer et al, 2008). Such species dependent differences in key foliar physiological properties are also linked to practical morphological and anatomical constraints such as variations in leaf and palisade layer thickness and exposure of mesophyll surface area to the intercellular airspaces (Kenzo et al, 2006). That is not to say, of course, that both within-species variability and the modulation of key physiological traits by the environment does not occur.…”
Section: Gradients In Nitrogen Phosphorus and Photosynthetic Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study we observed a significant increase of LMA with the sequence of ASDs in juvenile T. melinonii and to a lesser extent D. guianensis. Such an increase can be attributed to different factors: (i) Increased thickness, in particular of the palisade parenchyma as observed by Kenzo et al (2006) in some dipterocarp species. This was probably the case in T. melinonii (and to a lesser extent in D. guianensis) where leaf thickness increased with ASDs; (ii) Increased leaf density due to enhanced investment into structural support required to sustain larger lamina (Lusk and Warton, 2007 and references therein); increased density was indeed recorded in T. melinonii but again not in D. guianensis; (iii) Increased structural complexity due to the occurrence of branching may lead to restrictions of water supply to leaves due to hydraulic constrictions at branch bases; they may constrain leaf growth and result in smaller leaves (Niinemets, 2002;Thomas and Winner, 2002).…”
Section: Dicorynia Guianensismentioning
confidence: 99%
“…1987) for determining water use efficiency, which is reflected in the water status of the plant which can be measured through the water potential. The stomatal control and water status of plants change in accordance with the climatic conditions so they vary throughout the day (Pandey et al, 2003) and throughout the phenological cycle of plants (Thomas and Winner, 2002;Kenzo et al, 2006). The use of light by the photosynthetic apparatus is measured through chlorophyll fluorescence, allowing for the understanding of processes such as the photoinhibition caused by excess radiation that affects photosystems, causing chronic or dynamic damage (Aro et al, 1993).…”
Section: Introductionmentioning
confidence: 99%